2001
DOI: 10.1143/jjap.40.6945
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Self-Assembled Monolayer of Thiophene on Gold Surface: An Infrared Spectroscopic Study

Abstract: The growth process of self-assembled monolayers (SAMs) of thiophene on Au(111) surfaces was revealed by Fourier-transform infrared reflection absorption spectroscopy (FT-IR-RAS). Thiophene spontaneously adsorbs from an ethanol solution onto the gold surface, and forms well-ordered SAM. FT-IR-RAS measurements and Langmuir adsorption isotherms revealed that thiophene SAMs possess two phases with different molecular orientations during SAM growth. In the primary phase, thiophene orients parallel to the gold surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…The thiophene molecule without the S 1 atom is known to form the stable SAM on the Au(1 1 1) surface with standing on the S atom in it [18,19]. It is suggested that the interaction between the orbitals originated in this S atom and those of the surface Au atoms plays an important role in the adsorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiophene molecule without the S 1 atom is known to form the stable SAM on the Au(1 1 1) surface with standing on the S atom in it [18,19]. It is suggested that the interaction between the orbitals originated in this S atom and those of the surface Au atoms plays an important role in the adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to examine the interaction between the S 2 atom and the surface Au atoms. The fact that thiophene stably forms SAM on the Au(1 1 1) surface with standing on the S atom in it [18,19] implies that the interaction between S and Au plays a role in the adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…According to Higai's theoretical result of a TT molecule on the Au(1 1 1) surface, thiol-S atoms bound to the Au surface are more energetically stable than the adsorption of the thiophene-S atoms [8]. The thiophene moiety in a SAM of another thiophenethiol derivative was exposed at the surface, and the thiol group must be located near the Au surface to form a chemical bond with the Au surface [15].…”
Section: Adsorption Statesmentioning
confidence: 99%
“…Among them, SAMs of thiophene derivatives are one of the most fascinating systems for application to molecular electronics [4][5][6][7]. Although a thiophene SAM on a Au(1 1 1) surface can be prepared by a self-assembly method in solution [8][9][10][11], its adsorption energy is expected to be weak [12] and thermal decomposition of thiophene occurs in the SAM prepared from the solution [13]. A thiophenethiol derivative is another candidate for fabrication of a thiophene monolayer [14][15][16], since the thiol-S atoms are expected to be firmly bound to the Au surface so that the thiophene is ordered at the surface side.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when thiophene and thiol groups are present in the same molecule, the adsorption kinetics can become more complicated. [20] However, due to the much stronger binding energy between thiol and gold, it is not remote to assume that the thiophene moiety is less efficiently chemisorbed compared to organothiols in a competitive self-assembling process. [21][22][23][24] The interest in the adsorption properties of thiophenes onto electrode metals is also relevant due to their wide use in electropolymerization processes.…”
Section: Introductionmentioning
confidence: 99%